Theoretical study to find the thermal stress and strain generated in the Wood silica using lasers (Baghdad Science Journal, 2005)
In this research study theory to find the stress and emotion gases in the glass as a result of exposure to pulses of the laser beam has been the study using vehicles three major on-system axes cylindrical (r, 0, z), where I took three models of glass silica glass soda glass fused and shedtwo types of lasers where the study showed that the thermal stresses and emotions ...